Identification and Evaluation of Strain B37 of Bacillus subtilis Antagonistic to Sapstain Fungi on Poplar Wood - XiaoHua Zhang; GuiHua Zhao; DeWei Li; ShunPeng Li; Qing Hong (The Scientific World Journal)
Devaluation of poplar products by sapstain accounts for huge and unpredictable losses each year in China. We had isolated four poplar sapstain fungi, Ceratocystis adiposa Hz91, Lasiodiplodia theobromae YM0737, L. theobromae Fx46, and Fusarium sp. YM05, from five poplar varieties and 13 antagonistic bacteria from nine diverse varieties. After being experimented with agar plates, wood chips, and enzyme activities, strain B37 was identified as the best poplar sapstain biocontrol bacterium. The strain B37 was identified as Bacillus subtilis using sequences of the 16S rRNA gene, physiological biochemical, and morphological characteristics.